Efektifitas Self-Healing untuk Mengurangi Nyeri pada Ibu Bersalin di PMB Winda Nainggolan Kabupaten Simalungun Sumatera Utara - Winda Nainggolan; Lasria Simamora; Lisa Putri Utami Damanik; Ariska Fauzianty (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the causes of the high Maternal Mortality Rate (AKI) is long childbirth. If the delivery process lasts a long time, it can cause the mother to be exhausted because she runs out of energy. This results in inadequate uterine contractions (his) so that it can cause failure in the progress of labor. In addition to the inadequacy of uterine contractions (his), psychological conditions are also one of the factors that affect the length of labor progress. The psychological condition in question is the mother's perception of anxiety and pain during the childbirth process. One of the non-pharmacological therapies is self-healing , which is one of the methods used to manage emotions in order to avoid things that cause stress. This study aims to analyze the Effectiveness of Self-Healing to Reduce the Intensity of Pain in Maternal Mothers at PMB Winda Nainggolan, Hutabayu District, Simalungun Regency, North Sumatra Province in 2024. This research method uses a quantitative research approach with a quasi-experimental design research method in one group (one group prestest posttest). The research will be conducted in May 2024-July 2024. The sample size was 16 people with nonprobability sampling techniques. The data analysis used was using the Pairet t Test with an error value of α 0.05. The results of the study based on the output test statistics obtained a significance value of 0.000 which is smaller than the significance level of 5% (p-value = 0.000 < 0.05). The conclusion of the study is that Ha is accepted, which means that there is an effect of self-healing on the reduction of Period I labor pain in Primigravida mothers at PMB Winda Nainggolan, Hutabayu District, Simalungun Regency, North Sumatra Province in 2024. It is hoped that health workers can improve the quality of service, self-healing can be an intervention as one of the non-pharmacological therapies for maternal mothers.